(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2012)
A review of Charles A. Kupchan. No One’s World: The West, the Rising Rest, and The Coming Global Turn. A Council on Foreign Relations Book. (New York: Oxford University Press, 2012)